Developmental and life-course explanations of offending. Issue 6 (3rd July 2019) - McGee, Tara Renae; Farrington, David P.
ABSTRACT: Developmental and life-course theories of crime collectively can be viewed as theories which take an age-graded approach to explaining the development of offending based on empirical observations from prospective longitudinal studies. This paper provides not only an account of the key developmental and life-course theories of crime but also moves beyond this to include a comparison of the key postulates of these theories. To do this we first provide a brief account of the origins of developmental and life-course criminology and identify the theoretical origins in classic criminological theory. We also provide a brief description of some of the most prominent developmental and life-course theories of crime. This is all to set the stage for an extensive comparison of the key postulates of developmental and life-course theories. We argue that, in order to move forward with these theories, there must be systematic empirical testing of the key postulates to determine which parts of the theories are empirically supported and which parts need updating or revision.